Three Migrations. The Short Presentation of The Origins of Buddhism in Tibet And Its Impact on Tibetan Culture With Particular Reference to The Idea of The Dharma Protectors - Bierzyński, Zbigniew (Migracja w języku, literaturze i kulturze, 2020)
In this article it is assumed that migration (in its literally and metaphorical meaning) had significant impact on the Tibetan spirituality. The main aim of this article is to bring closer figure and function of Dharma Protectors (Sanskrit: dharmapala), whose roots have grown out of the pre-Buddhist times. The first migration is connected with the origins of Buddhism on the Roof of the World (activity of Guru Padmasambhava, king Songtsen Gampo and his wives Bhrikuti and Wencheng). That has caused the evolution of Himalayan native deities to the Dharma Protectors. This transformation has resulted in the second migration – metaphorical journey of shamanic deities into the Buddhist monasteries. Many legends and myths are telling about it. Their examples are presented and explained shortly. Finally, the third migration – caused by the Chinese invasion on Tibet – is associated with the mysterious prophesy of Guru Padmasambhava and the question of migration’s influence on the future Tibetan generations.